A pragmatic approach for a 3D material model considering elasto-plastic behaviour, damage initiation by Puck or Cuntze and progressive failure of fibre-reinforced plastics. (August 2020) - Völkerink, O.; Petersen, E.; Koord, J.; Hühne, C.
Highlights: 3D material model for FRPs considering elasto-plastic behaviour and progressive damage. Model components selected with regard to minimised characterisation and computing effort. Accurate prediction of the failure behaviour of open-hole tension specimens made out of AS4/PEEK. Comparison of the failure theories of Cuntze and Puck in terms of accuracy and computing time. Abstract: Fibre reinforced plastics with tough epoxy and thermoplastic matrices are spreading increasingly in many lightweight applications. For an efficient and reliable design the mechanical behaviour, considering non-linear plasticity, various failure modes under complex loading and damage progression, has to be estimated with numerical simulations. Most state-of-the-art continuum damage mechanics models do not consider the non-linear behaviour of the matrix material or are not suited for 3D solid elements. This work proposes a combined 3D continuum damage/plasticity model. It uses a single parameter flow criterion in combination with Cuntze's Failure Mode Concept (FMC) for intralaminar failure. The FMC requires no iterative fracture angle search as the Action Plane Strength Criterion by Puck (APSC). This work describes details of the developed model like the coupling of the FMC with a degradation model as well as the implementation into Abaqus/Standard. A validation against open-hole tension tests made out of AS4/PEEK from literature is performed. It can be shown that the prediction of experimental failure loads with the FMC as well as with the APSC provides comparable results. The maximum deviations are between - 7.85 % and + 12.85 % . However, the computation times for predictions with the FMC are significantly less than with the APSC.